2022
DOI: 10.1177/07308884211060765
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant–Native Wage Gaps at Work: How the Public and Private Sectors Shape Relational Inequality Processes

Abstract: We investigate how the institutional context of the public and private sectors regulates the association of workplace diversity policies and relational status positions with first- and second-generation immigrants’ wages. Using unique linked employer–employee data combining administrative and survey information of 6,139 employees in 120 German workplaces, we estimate workplace fixed-effects regressions. Workplace processes are institutionally contingent: diversity policies such as mixed teams reduce inequaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
0
10
2
Order By: Relevance
“…However, large private companies often exhibit more bureaucratic organizational structures and more often adopt formalized employment procedures, which are likely to reduce the scope of discriminatory organizational processes (Marsden, Cook and Kalleberg 1996). Moreover, prior research has shown that unionization and more centralized and standardized wage bargaining reduce immigrantnative wage differentials (Drange andHelland 2019, Peters andMelzer 2022). Thus, we expect immigrant-native pay gaps to be lower in more bureaucratized organizational contexts.…”
Section: Variation Across the Labor Market: Meritocracy And Bureaucra...mentioning
confidence: 80%
See 1 more Smart Citation
“…However, large private companies often exhibit more bureaucratic organizational structures and more often adopt formalized employment procedures, which are likely to reduce the scope of discriminatory organizational processes (Marsden, Cook and Kalleberg 1996). Moreover, prior research has shown that unionization and more centralized and standardized wage bargaining reduce immigrantnative wage differentials (Drange andHelland 2019, Peters andMelzer 2022). Thus, we expect immigrant-native pay gaps to be lower in more bureaucratized organizational contexts.…”
Section: Variation Across the Labor Market: Meritocracy And Bureaucra...mentioning
confidence: 80%
“…Second, we assess variation in immigrant-native wage inequality by immigrant generation and origin country. Only a few prior studies using linked-employer employee data have focused on children of immigrants (Lillehagen and Hermansen 2022, Melzer et al 2018, Peters and Melzer 2022. In particular, Melzer et al (2018) found, on average, only small wage penalties net of human capital among second-generation immigrants, but with substantial variation in the immigrant-native wage gaps across workplaces.…”
mentioning
confidence: 99%
“…Policy makers and social scientists alike show increasing interest in the consequences of rising ethnic diversity and the growing presence of immigrant-background workers for organizational inequality and ethnic stratification in European and North American labor markets (DiTomaso, Post and Parks-Yancy 2007, Dostie et al 2021, Drouhot and Nee 2019, Heath and Cheung 2007, Peters and Melzer 2022, Tomaskovic-Devey, Hällsten and Avent-Holt 2015. However, increasing numbers of immigrant minorities in the workforce will not necessarily lead to increased exposure between immigrant-background ethnic minorities and the native-born ethnic majority at work, since ethnic workplace segregation is often widespread (Andersson et al 2014, Glitz 2014, Hellerstein and Neumark 2008, Lillehagen and Hermansen 2022, Strömgren et al 2014, Åslund and Skans 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Immigrants and their native-born descendants typically earn less than native-born majority workers in ethnic diverse countries in Europe and North America (Alba and Foner 2015;Algan et al 2010;Heath and Cheung 2007). The immigrant-native pay gap can be traced all the way down to the workplace (Åslund, Hensvik, and Skans 2014;Tomaskovic-Devey, Hällsten, and Avent-Holt 2015;Grinza, Kampelmann, and Rycx 2020;Dostie et al 2020;Joshi, Liao, and Jackson 2006;Melzer et al 2018;Peters and Melzer 2022) where social relations, categorization, and access to power within workplaces are the central inequality-generating processes to explain the persistency of this gap (Baron and Bielby 1980;Stainback, Tomaskovic-Devey, and Skaggs 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about how such labor market institutions influence wage setting processes within workplaces. As the organizational perspective of relational inequality theory (RIT) argues for the salience of categorical distinctions in the distribution of workplace resources (Peters and Melzer 2022), it will require strong institutional and legal regulations to effectively curb these inequality-generating organizational tendencies. Against this background, we ask how do the size of the immigrant-native wage gaps vary with the workplace shares of licensed and unionized employees?…”
Section: Introductionmentioning
confidence: 99%